Can thyroid surgery be decided based on ultrasonographic findings, irrespective of cytopathological findings? Five-year retrospective study in a district general hospital. Issue 2 (February 2017) - Elsayed, A.A.; Murdoch, C.; Murray, S.; Bashir, K.
Abstract : Aim: To evaluate whether thyroid surgery be decided based on ultrasonographic criteria of the nodule(s), irrespective of cytopathological findings. Materials and methods: The histopathological findings of resected thyroid lobes were retrospectively reviewed and the findings were compared with the preoperative ultrasonographic and cytopathological findings. Results: The results suggest that the decision to operate on thyroid lesions based on suspicious sonographic findings was correct in a significant number of patients irrespective of the preoperative cytopathological findings. Conclusion: Sonographic features suspicious for malignancy should be taken seriously even if the cytopathological results are inconclusive or are suggestive of benignity. Highlights: Role of Ultrasonography in the characterization of thyroid nodules. Correlation of Ultrasonography and Fine Needle Aspiration Cytology with postoperative histopathological findings. Role of Ultrasound and cytopathology in thyroid surgery decision making.